MAP4K4 and cancer: ready for the main stage? - González-Montero, Jaime; Rojas, Carlos I.; Burotto, Mauricio (Frontiers in Oncology, 2023)
MAP4K4 is a serine/threonine kinase that belongs to the MAP kinase family and plays a critical role in embryogenesis and cellular migration. It contains approximately 1,200 amino acids and has a molecular mass of 140 kDa. MAP4K4 is expressed in most tissues where it has been examined and its knockout is embryonic lethal due to impaired somite development. Alterations in MAP4K4 function have a central role in the development of many metabolic diseases such as atherosclerosis and type 2 diabetes, but have recently been implicated in the initiation and progression of cancer. For example, it has been shown that MAP4K4 can stimulate the proliferation and invasion of tumour cells by activating pro-proliferative pathways (such as the c-Jun N-terminal kinase [JNK] and mixed-lineage protein kinase 3 [MLK3] pathways), attenuate anti-tumour cytotoxic immune responses, and stimulate cell invasion and migration by altering cytoskeleton and actin function. Recent in vitro experiments using RNA interference-based knockdown (miR) techniques have shown that inhibition of MAP4K4 function reduces tumour proliferation, migration, and invasion, and may represent a promising therapeutic approach in many types of cancer such as pancreatic cancer, glioblastoma, and medulloblastoma, among others. Over the last few years, specific MAP4K4 inhibitors such as GNE-495 have been developed but have not yet been tested in cancer patients. However, these novel agents may be useful for cancer treatment in the future.